2019
DOI: 10.1021/acsnano.8b09223
|View full text |Cite
|
Sign up to set email alerts
|

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands

Abstract: Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (∼10 12 cm Hz 1/2 /W) and a cutoff frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…In this case, small nanocrystals (3-4 nm) are used. To reach the SWIR range 27,28 , larger nanocrystals around 8 nm are necessary. Such sizes are nevertheless acceptable to obtain colloidally stable solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, small nanocrystals (3-4 nm) are used. To reach the SWIR range 27,28 , larger nanocrystals around 8 nm are necessary. Such sizes are nevertheless acceptable to obtain colloidally stable solutions.…”
Section: Introductionmentioning
confidence: 99%
“…25,31 Mora-Seró and co-workers observed a tunable exciplex emission from QD -MHPs for designing intermediate-band photovoltaics and NIR LEDs and detectors. [32][33][34][35] More recently, epitaxial seeding of PbS QDs in MHPs has enabled "lattice anchoring" to strain and stabilize a thermodynamically unstable phase of CsPbI 3-x Br x in ambient. 26 Additionally, PbS QDs in MHP single crystals have shown promise for use in resistive switching.…”
mentioning
confidence: 99%
“…For the subnano thickness of the perovskite shells, they are sometimes referred to as perovskite ligands. [138,152] The reversestructured perovskite-PbS core-shell heterojunctions were not revealed until 2018. Zhang et al reported the synthesis of thin PbS shell-capped CsPbI 3 NCs (Figure 19c).…”
Section: Subnanometric Heterojunctions: Inorganicmentioning
confidence: 99%